2015
DOI: 10.1111/1911-3838.12044
|View full text |Cite
|
Sign up to set email alerts
|

The Israeli XBRL Adoption Experience

Abstract: eXtensible Business Reporting Language (XBRL) is a language for the electronic communication of business and financial data which is revolutionizing business reporting around the world. It is a tool to bridge potential language barriers and unify financial reporting. This has appeal to foreign investors, among others, who can rely on information in XBRL-tagged financial reports to make investment decisions without having to translate financial statements from local language. In 2008, Israel required most publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…xbrl.org/), research papers (such as Peng, Shon, & Tan, 2011;Yoon, Zo, & Ciganek, 2011;Bai, Sakaue, & Takeda, 2014;Markelevich, Shaw, & Weihs, 2015;Liu, Luo, & Wang, 2017), reports published by members of the XBRL International organization (such as O'Kelly, 2010) and the Ministry of Corporate Affairs of India website (www.mca.gov.in/XBRL). The World Bank website was used to collect data of our dependent variable stock market development and the following control variables: stock market liquidity, the development of the banking sector, the level of investment, macroeconomic stability, and economic growth.…”
Section: Methodology Our Samplementioning
confidence: 99%
See 1 more Smart Citation
“…xbrl.org/), research papers (such as Peng, Shon, & Tan, 2011;Yoon, Zo, & Ciganek, 2011;Bai, Sakaue, & Takeda, 2014;Markelevich, Shaw, & Weihs, 2015;Liu, Luo, & Wang, 2017), reports published by members of the XBRL International organization (such as O'Kelly, 2010) and the Ministry of Corporate Affairs of India website (www.mca.gov.in/XBRL). The World Bank website was used to collect data of our dependent variable stock market development and the following control variables: stock market liquidity, the development of the banking sector, the level of investment, macroeconomic stability, and economic growth.…”
Section: Methodology Our Samplementioning
confidence: 99%
“…Although some studies demonstrated that the adoption of the XBRL is very beneficial and has positive consequences (Hodge, Kennedy, & Maines, 2004;Tan & Shon, 2009;Yoon, Zo, & Ciganek, 2011;Chen, 2012;Bai, Sakaue, & Takeda, 2014;Markelevich, Shaw, & Weihs, 2015;Tzu-Yi et al, 2016;Blankespoor, 2019;Kumar, Kumar, & Dilip, 2019;Rahwani et al, 2019), there is still a need to examine the its usefulness at the country level (Nobre & Carvalho, 2011;Steenkamp & Nel, 2012). For example, Cong, Hao, and Zou (2014) provided empirical evidence that XBRL adoption improves stock market efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The article additionally extends existing knowledge of Inline XBRL by shedding light on the process of producing Inline XBRL-formatted financial statements in the new regulatory context. While a large and growing body of literature has investigated the XBRL standard adoption (e.g., Pinsker & Li 2008;Felden 2011;Steenkamp & Nel 2012;Henderson et al 2012;Markelevich et al 2015;Ilias & Ghani 2015), there is still very little scientific understanding of XBRL and Inline XBRL implementation (e.g., Sledgianowski et al 2010b;Janvrin & No 2012;Hsieh et al 2019;Cong et al 2019). Thus, despite its exploratory nature, this study may lay the valuable groundwork for future research by providing the initial feedback on the transposition of ESEF requirements into financial reporting procedures and practices from the preparers' standpoint.…”
Section: Introductionmentioning
confidence: 99%
“…XBRL, an acronym of eXtensible Business Reporting Language, is an open standard to report financial and business information electronically [3] that enable the preparation, publication, exchange, and analysis of the financial and business statement [4]. Since introduced in the early 2000, XBRL has been already implemented in several countries such as the Netherlands [5], Australia [6], the United States [7], the United Kingdom [8], China [9], India [10], South Korea [11], Israel [12], Saudi Arabia [3] and Italy [13].…”
Section: Introductionmentioning
confidence: 99%